2018
DOI: 10.1371/journal.pone.0193088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of clinical trial status discrepancies: A cross-sectional study of 10,492 trials registered on both ClinicalTrials.gov and the European Union Clinical Trials Register

Abstract: ObjectiveTrial registries are a key source of information for clinicians and researchers. While building OpenTrials, an open database of public trial information, we identified errors and omissions in registries, including discrepancies between descriptions of the same trial in different registries. We set out to ascertain the prevalence of discrepancies in trial completion status using a cohort of trials registered on both the European Union Clinical Trials Register (EUCTR) and ClinicalTrials.gov.Study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…At the same time, Reveiz et al reported lack of methodological information in RCTs of seven international registries, and Kosa et al reported the disagreement in methodological information between publication and registry . Also, Fleminger et al describe the inaccuracy on completion status between Clinicaltrials.gov and the European registry . REPEC's registries do not report methodological and intervention characteristics before 2011.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Reveiz et al reported lack of methodological information in RCTs of seven international registries, and Kosa et al reported the disagreement in methodological information between publication and registry . Also, Fleminger et al describe the inaccuracy on completion status between Clinicaltrials.gov and the European registry . REPEC's registries do not report methodological and intervention characteristics before 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we searched clinical trials registered through ClinicalTrials.gov, which could potentially exclude some studies. There are other clinical trial databases such as EU Clinical Trials Register, however, the ClinicalTrials.gov database reports more accurate and updated information for clinical trials [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…Completion dates are entered as expected dates and might not always reflect the actual completion dates. As registries are increasingly consulted as a key resource for health care information and for quality assessment of research practices it is important to improve their quality, accuracy and timeliness [30]. We published a more detailed commentary on how different measurement variables influence the assessment of publication rates elsewhere [31].…”
Section: Discussionmentioning
confidence: 99%